Implikatur Percakapan dalam Film Nihonjin No Shiranai Nihongo - Timur Sri Astami (Humaniora, 2014)
Speech acts learns about the relationship between speaker and hearer. It needs good cooperation between speaker and hearer so that communication can run well. A speech has implicatures depending on what is heard by the hearer. This researh aims to find implicatures in Nihonjin no Shiranai nihongo Ep 1 movie. Research applied qualitative approach with descriptive analysis. Then, by its results, it is found conversational implicatures, such requests, questions, suspicion, doubt, sadness, sarcasm, ridicule, orders, facts, and solicitation occurred in the movie. Moreover, research concludes that the implicatures happened in directive, expressive, declarative, and assertive speech act.